2021
DOI: 10.3390/nano11092421
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles and Their Applications in Harvesting Sunlight for Solar Thermal Generation

Abstract: Silver (Ag) nanoparticles (NPs) have been synthesized through an easy, inexpensive, and ecofriendly method. Petroselinum crispum, parsley, leaf extract was utilized as a reducing, capping, and stabilizing agent, without using any hazardous chemical materials, for producing Ag NPs. The biosynthesized Ag NPs were characterized using different characterization techniques, namely UV-Vis, FT-IR spectroscopy, X-ray diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), dynamic light scattering (DLS), zeta potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 124 publications
(155 reference statements)
4
30
1
Order By: Relevance
“…Moreover, under slightly basic conditions (pH 8), the SRP p redshifted to 540 nm, hence implying the formation of AgNPs that are larger in [16,26]. However, our results are inconsistent with a previous study that repo The absorption bands at 400-450 nm confirmed the formation of AgNPs [14,24]. Furthermore, the spectra also revealed that the formation of AgNPs were favorable under slightly acidic (pH 5-6) and neutral (pH 7) conditions.…”
Section: Biosynthesis Of Silver Nanoparticlescontrasting
confidence: 99%
“…Moreover, under slightly basic conditions (pH 8), the SRP p redshifted to 540 nm, hence implying the formation of AgNPs that are larger in [16,26]. However, our results are inconsistent with a previous study that repo The absorption bands at 400-450 nm confirmed the formation of AgNPs [14,24]. Furthermore, the spectra also revealed that the formation of AgNPs were favorable under slightly acidic (pH 5-6) and neutral (pH 7) conditions.…”
Section: Biosynthesis Of Silver Nanoparticlescontrasting
confidence: 99%
“…The existing water-soluble polyphenolic molecules in Cynara cardunculus extract successfully reduced the available silver metal ion (Ag + ) to metallic silver nanoparticles (Ag 0 ) [ 53 ]. The bioreduction of metal ions to metallic nanoparticles takes place through an activation step, which involves the reduction of available silver metal ions followed by the nucleation and growth steps in which metal nanoparticles of definite shapes and sizes are formed [ 54 ]. Finally, the stabilization step takes place, in which the Cynara cardunculus extract metabolites similarly play the role of surface-capping agents to prevent the nanoparticles from agglomerating [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bioreduction of metal ions to metallic nanoparticles takes place through an activation step, which involves the reduction of available silver metal ions followed by the nucleation and growth steps in which metal nanoparticles of definite shapes and sizes are formed [ 54 ]. Finally, the stabilization step takes place, in which the Cynara cardunculus extract metabolites similarly play the role of surface-capping agents to prevent the nanoparticles from agglomerating [ 54 ]. The proposed mechanism of CC-AgNPs formation via Cynara cardunculus extract is depicted in systematic Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The novelty of this study is that it used green synthesis to manufacture SiO 2 NPs from their first product (Na 2 SiO 3 ), completing their approach entirely using green synthesis. This investigation is our ongoing study in the green synthesis NPs area [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%